Metaverse beyond the hype: Multidisciplinary perspectives on emerging challenges, opportunities, and agenda for research, practice and policy. (October 2022) - Dwivedi, Yogesh K.; Hughes, Laurie; Baabdullah, Abdullah M.; Ribeiro-Navarrete, Samuel; Giannakis, Mihalis; Al-Debei, Mutaz M.; Dennehy, Denis; Metri, Bhimaraya; Buhalis, Dimitrios; Cheung, Christy M.K.; Conboy, Kieran; Doyle, Ronan; et al.
Abstract: The metaverse has the potential to extend the physical world using augmented and virtual reality technologies allowing users to seamlessly interact within real and simulated environments using avatars and holograms. Virtual environments and immersive games (such as, Second Life, Fortnite, Roblox and VRChat) have been described as antecedents of the metaverse and offer some insight to the potential socio-economic impact of a fully functional persistent cross platform metaverse. Separating the hype and "meta…" rebranding from current reality is difficult, as " big tech " paints a picture of the transformative nature of the metaverse and how it will positively impact people in their work, leisure, and social interaction. The potential impact on the way we conduct business, interact with brands and others, and develop shared experiences is likely to be transformational as the distinct lines between physical and digital are likely to be somewhat blurred from current perceptions. However, although the technology and infrastructure does not yet exist to allow the development of new immersive virtual worlds at scale - one that our avatars could transcend across platforms, researchers are increasingly examining the transformative impact of the metaverse. Impacted sectors include marketing, education, healthcare as well as societal effects relating to social interaction factors from widespread adoption, and issues relating to trust, privacy, bias, disinformation, application of law as well as psychological aspects linked to addiction and impact on vulnerable people. This study examines these topics in detail by combining the informed narrative and multi-perspective approach from experts with varied disciplinary backgrounds on many aspects of the metaverse and its transformational impact. The paper concludes by proposing a future research agenda that is valuable for researchers, professionals and policy makers alike. Highlights: The metaverse has the potential to extend the physical world using extended, augmented, and virtual reality technologies. Interactive virtual environments and immersive games are considered as antecedents of the metaverse. The transformative impact of the metaverse as well as societal effects relating to social interaction factors from widespread adoption. Sectors potentially impacted by the metaverse include marketing, education, tourism, and healthcare.